Growth Mechanism and Characterization of PbTe0.5Se0.5 Thin Films Used by Closed-Space Vapor Transport in a Vertical Reactor - Yanuar Hamzah; Jimmy Copriady; Ariswan Ariswan (Dept. of Chemical Engineering, Diponegoro University, 2019)
A simple method for growing thin film of semiconductor material PbTe0.5Se0.50 has been designed using the vapor transport (CSVT) method in a vertical reactor. The objectivity of this method is to study thin film growth formation due to chemical reactions during the deposition process in the reactor. In this study will describe some formations the vapor transport mechanism of PbTe0.5Se0.50 semiconductor material using iodine gas (I2) to accelerate the etching reaction on the substrate surface. Next, we will describe how the mechanism of the reaction in the reactor zone for growing thin films on the substrate. The thin films were characterized by structural, morphology properties and its composition. The film structure is a cubic structure with the maximum diffraction intensity at peak (222). The surface morphology of the thin film has a microcubes shape with a grain size 10 to 20 mm. Keywords: etching reaction; micro-cube; PbTe0.5Se0.50; close-spaced vapor transport